THE MENACE OF COVID-19: SURVIVAL STRATEGIES FOR SMALL AND MEDIUMSCALE ENTERPRISES IN NIGERIA - Michael Okon Essien; Emmanuel Sunday Ukpong; Ime Robson Nseobot; Clement Efiong Okon; Ikoroha Innocent Simeon; Anietie Imo Effiong; Vinesh Dinnoo; Uduakabasi Ana Eyo (Bina Nusantara University, 2020)
Small and Medium Enterprises (SMEs) have been considered as the engine of economic growth and for promoting equitable development all over the world. The Coronavirusdisease(COVID-19) pandemic has caused unprecedented panic, disruptions and lossesfor businesses. This is why this paper investigatesthe survival strategy for Small and Medium Enterprises (SMEs) in Nigeria after COVID-19 pandemic.The concept of Small and Medium Enterprises,history and advances of COVID-19 pandemic in Nigeria, Small and Medium Scale SMEs capacity building in Nigeria, government’sresponse to the pandemic: a global perspective and steps SMEs must take to survive post COVID-19 were discussed. The study concluded that there is no gainsaying that Small and Medium Enterprises (SMEs) are the backbone of any economy globally. This subject has been resounded everywhere throughout the world! The time is now to step up and do what we allknow is the appropriate course of action.The paper recommended among others thatSmall and Medium Enterprises (SMEs) should approach commercial banks, or the Bank of Industry for loans to keep them afloat, at reduced interest rates.